Assesment of Opinions of Forensic Science Experts and Technicians On Global Pandemic Management Strategies Through SarsCov2 Pandemic - MELEZ, İPEK ESEN; Ulutaş M.; Melez İ. E.; Arslan M. (My University, 2022)
This study was implemented to assess the opinions of forensic science experts and techni cians of The Ministry of Justice Council of Forensic Medicine on global pandemic management strategies including new technologies and future scenarios through SARSCov2 pandemic. This prospective and descriptive research was carried out with a questionnair e that was asked to 244 personnel (forensic medicine specialist, forensic medicine resident, technician, other specialist from a different field, other specialist phsician) working at The Ministry of Justice Council of Forensic Medicine. The 40question su rvey included questions about participants’ level of knowledge perception about the pandemic and attitudes on measurestheir adequacynecessity, technological applications and the future of global management strategies. 93.8% (n=229) of the participants th ought they had knowledge about the pandemic and its transmission routes, 54.1% (n=132) found the applied pandemic management strategies effective and correct, and 76.6% (n =187) stated that it is necessary to use technological infrastructures in future sce narios. As a result, through hundreds of descriptive statictics results in 80 tables classified according to education level, occupation type and occupational experience level, in general, despite the changes in group tendencies according to different fact ors, the majority of participants were found to be obeying the routine necessities of the pandemic, hesitating on the global strategies, feeling closer to habitual technologies, feeling far to technologies which have never experienced before in daily life, giving answers with a high ratio of \"no opinion\" due to feeling obliged to give decisions gropely among unproven propabibilities or due to their hesitation on sharing their opinion even if they had an opinion. Moreover according to results, it was interpr eted that social engineering could easily be performed in any spesifically designed group.
Keywords: Tıp; Dahili Tıp Bilimleri; Adli Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Forensic Medicine (Medical Jurisprudence); Health Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, YASAL; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, LEGAL; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Sorunlar, Etik ve Hukuki Yönler; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Issues, Ethics and Legal Aspects; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine